2014
DOI: 10.1002/eco.1545
|View full text |Cite
|
Sign up to set email alerts
|

Water uptake and hydraulic redistribution under a seasonal climate: long‐term study in a rainfed olive orchard

Abstract: Hydraulic redistribution plays a relevant role in the water relations of trees in climates with alternation between warm/dry and cold/wet periods. We aim to illustrate the ability of Mediterranean deep‐rooted rainfed olive trees to maintain transpiration during the hot dry season and to redistribute soil water through roots, tending to temporarily homogenize soil moisture vertically. Sap flow was monitored by the heat field deformation method for 2·5 years in the stem, lignotuber, medium and shallow roots of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 46 publications
0
17
1
8
Order By: Relevance
“…These results were consistent with Tron et al's [122] findings, in that plants characterized by a cooperative root system seemed to be less prone to water stress while plants with non-interacting roots appeared to better thrive in climates with less probability of drought. By cooperative root systems, those researchers included the possibility of hydraulic redistribution in the root systems (as described in [123] for olive).…”
Section: Comparing Experimental Ks Functionsmentioning
confidence: 99%
“…These results were consistent with Tron et al's [122] findings, in that plants characterized by a cooperative root system seemed to be less prone to water stress while plants with non-interacting roots appeared to better thrive in climates with less probability of drought. By cooperative root systems, those researchers included the possibility of hydraulic redistribution in the root systems (as described in [123] for olive).…”
Section: Comparing Experimental Ks Functionsmentioning
confidence: 99%
“…Therefore, during the driest periods of the year, Δ⟨ s ⟩ tends to decrease towards zero. This trend was similar to the seasonal sap flow measured by Nadezhdina et al () in shallow roots of olive trees.…”
Section: Discussionmentioning
confidence: 99%
“…Hupet and Vanclooster, ) or non‐agricultural land uses (Teuling and Troch, ; Teuling et al, ; Lebron et al, ; Liang et al, ; Jost et al, ), few studies have addressed the influence of olive trees on soil moisture dynamics. As an exception, Nadezhdina et al () showed that olive trees control moisture dynamics in the rhizosphere during the dry summer‐season via water redistribution into the soil profile. Other studies have also shown that moderately size trees, such as olives, control moisture dynamics through canopy interception and shading (Williams and Albertson, ), water uptake (Guswa, ; Nadezhdina et al, ) and structure modification by roots (Lebron et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The responses of spruce trees to seasonal drought stress are not limited to stem circumference, needle water potential and sap flow, but also include alteration of their mutual relations (Ježík et al, 2015). Conversely, plants can significantly contribute to the complex distribution of water in soil, which is demonstrated by Nadezhdina et al (2015): In climates with alternation between warm/dry and cold/wet periods, olive trees were found to maintain transpiration during the hot/dry season and to redistribute soil water through roots, which tended to temporarily form a more homogeneous vertical soil moisture distribution. The characteristics of plant species are crucial for the optimization of soil capping systems of waste piles with respect to maximum evpotranspiration and minimum drainage into the underlying hazardous waste However, under conditions of low vegetation coverage in dryland ecosystems, the possibility was found relatively limited (Arnold et al, 2015).…”
mentioning
confidence: 99%